“Evaluación del a variabilidad genética inducida por radiacion gamma en semillas de sacha inchi (plukenetia volubilis L.)” - Pezo Najar, Jean'S Marlon (2014)
The objective of the study was to generate genetic variability through mutation induction using gamma rays. The first phase of the study was conducted in the nursery of the Research lnstitute of the Peruvian Amazon, where was evaluated biometric and phenological characteristics of plants obtained using irradiated seeds. Before planting the seeds was realized dosimetry of the seeds to estímate the time to be used in the irradiation of each treatment. The irradiation was made with gamma rays of Cobalt 60. The experiment had 8 treatments and 1 control (2, 5, 1 O, 25, 50, 100, 200, y 400 gray) and we used 100 seeds per treatment. The seeds were planted under a completely randomized design with 4 repetitions and the results were subjected to a comparison test of means (Duncan = 5%). The second phase consisted in the molecular analysis with AFLP markers (Amplified fragment length polymorphism). This phase involved 4 steps: (1) DNA extraction was made from fresh leaves of sacha inchi, taking 5 samples per treatment, using the methodology of CTAB 2% (Doyle & Doyle, 1990); (2) determination of DNA quality and concentration; (3) PCR amplification using 4 primers and (4) polyacrylamide gel electrophoresis. This activity was conducted in the Molecular Biology Laboratory of the Biotechnology lnstitute (IBT) of the La Molina National Agrarian University - Lima. The results obtained in the phenological variables were taken from periodic evaluations for 60 days. Ali treatments show highly significant differences and the control (non-irradiated seeds) showed better performance and results in comparison to irradiated seeds; so the germination, emergence, survival and physiological capacity of the plants decreased with increasing radiation dose. In relation to the treatments that were exposed to radiation, the one that showed better results surpass all other treatments was T4 (10 gray). Treatments with doses greater than 25 gray increasing mortality showed a decline in the results. In the biometric variables, the control treatment (O gray) showed better results for the variable height and length of roots, while for the seeds irradiated, the treatment that generated greater gain in height (40.49 cm), number of leaves (9.83 leaves) and root length (17.06 cm) was T4 (10 gray). Other results indicate that when the intensity of gamma radiation is increasing there is a decrease in the ability of plant development, except in the diameter of plants that the results were directly proportional to the dose of gamma radiation used. The median lethal dose (DL50) to the irradiated seeds is in the T6 (50 gray), with a value of 51.58% of surviving plants. Finally, molecular analysis using AFLP markers shows that with 4 primers analyzed were obtained 7 polymorphic markers representing 6.2% of a total of 113 DNA bands amplified, indicating the generation of a moderate genetic variability through mutation induction by gamma rays.